2016
DOI: 10.1155/2016/1729147
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Anemia and Hematological Predictors among Children under 12 Years in Odisha, India

Abstract: Background. Anemia is a wide spread public health problem in India which affects children. The present study evaluates the prevalence of anemia and status of various hematological parameters among children of Khurda district, Odisha. Method. A total of 313 children aged 0–12 years were enrolled for the study which included preschool (0–5 years) and school aged (6–12 years) groups. Hematological indicators were measured by standard procedures, which include red blood cell (RBC) indicators, white blood cell (WBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
(39 reference statements)
4
21
1
Order By: Relevance
“…school‐aged children and elderly) were included. Sporadic studies have indicated that severe anaemia may be quite prevalent in such underrepresented vulnerable groups (~18% in school children aged 6 to 12 years from Odisha, ~15% in community‐dwelling elderly > 60 years from Assam) .…”
Section: Discussionmentioning
confidence: 99%
“…school‐aged children and elderly) were included. Sporadic studies have indicated that severe anaemia may be quite prevalent in such underrepresented vulnerable groups (~18% in school children aged 6 to 12 years from Odisha, ~15% in community‐dwelling elderly > 60 years from Assam) .…”
Section: Discussionmentioning
confidence: 99%
“…[16] Behera et al have documented prevalence of anaemia in 62 % kids in their study population in Orissa. [17] Anaemia affects the physical and mental development of children leading to decreased work capacity which in turn affects the development of the country. [7] Iron deficiency is one of the most common causes of anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of anemia has been reported to variously between 55% and 72%. [456789] In addition, most of the studies are limited to the infancy age group. [567] Prompted by this seemingly high prevalence of anemia among children under 5 years of age admitted to hospital for various reasons, combined with the fact that currently there is limited information on the prevalence and patterns of anemia among children, especially beyond infancy in Eastern India, we conducted this current hospital-based study to have a better understanding of the actual burden.…”
Section: Introductionmentioning
confidence: 99%